Plasma Exeresis Technology for Rejuvenation of the Upper Eyelid - Karapantzou, Chrisanthi; Vale, Joao Pedro; Haubner, Frank; Canis, Martin (Archives of Clinical and Medical Case Reports, 2022)
Background: One of the common aesthetic and functional surgical interventions is the upper eyelid blepharoplasty. It offers satisfying results, but is associated to some non-reversible complications. An non-surgical method for rejuvenation of the eyelid, is the usage of Plexr®. Based on plasma exeresis technology, it allows precise sublimation of epidermal and superficial dermal layers, without adverse events. This intrinsic plasma exeresis induces an immediate lifting effect of the treated skin. Methods: Objective of this clinical observational study, is to assess the long-term results in a 60 patients cohort (9 male, 51 female), where bilateral plasma blepharoplasty was performed under local anesthesia, in a period of 18 months. All participants were subjected to 2 interventions with Plexr®. 32 patients were treated in the ORL Department of the Interbalcan Medical Hospital in Thessaloniki and the rest of the cohort in the ORL University Department of the LMU in Munich. They were treated by the same physician, for the same indication: upper eyelid dermatochalasis, without lipoptosis. Photographs were taken prior to each session and after the second procedure. Parameters that were evaluated, were the reduction of the flaccened eyelid skin, the duration of post-treatment oedema, the development of wound healing and pain perception. Patient satisfaction was rated at 6 months, 12 months and 18 months post- procedure. Results: A very good general satisfaction rate with long-lasting results was reached, while no relevant adverse effects were reported. The treatment combined a quick, well tolerated procedure with a low downtime, compared to surgical blepharoplasty. Conclusions: Plasma technology is an effective method to rejuvenate the upper eyelid and manage